The Toxicity and Antibacterial Properties of Calamus ornatus Bl. Rattan Fruit - Heriad Daud Salusu; Ernita Obeth; Abdul Rasyid Zarta; Eva Nurmarini; Hamka Nurkaya; Irawan Wijaya Kusuma; Enos Tangke Arung (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Calamus ornatus Bl., locally known as rotan mantang or rotan seuti is one of the commercial rattan species growing in the forests of East Borneo. Its fruit is edible, like the fruits of other species of rattan, and it has been used by the local people as traditional medicine to treat stomachache or toothache. Until recently, there has not been any study investigating the benefits of the fruit for medicinal or other purposes. This research aimed to discover the bio-activity potentials of Calamus ornatus Bl. fruits by identifying its toxicity level and antibacterial potentials. The parts of the fruit (pericarp, flesh, and seed) were extracted using ethanol as solvent to extract samples. The toxicity was analyzed by using the Brine Shrimp Lethality Test (BSLT) method while the antibacterial activity was tested using a well diffusion method. Low toxicity was found in the flesh, whereas the pericarp and the seed were non-toxic. Antibacterial activity against Escherichia coli was found in the pericarp and the seed, while antibacterial activity against Streptococcus mutans was found in the pericarp and the flesh.